An Update on the Antifungal Activities of Lactoferrin: New Promising Applications in Diagnostic, Therapeutics and Biotechnology - Giansanti, Francesco; Leboffe, Loris; D'Elia, Ilaria; Antonini, Giovanni (Anti-Infective Agents, 2013)
Lactoferrin is an iron binding protein belonging to the transferrin superfamily. Its main function is the protection towards infections. In a previous article (Leboffe et al., Anti-Infective Agents in Medicinal Chemistry, 2009), we have reviewed the antifungal and antiparasitic activity of lactoferrin. In the present updated review we focused the attention on the newly discovered antifungal properties of lactoferrin and its derived peptides in clinical, diagnostic and biotechnological applications. In particular, we discuss the new findings on diagnosis of fungal infections utilizing Lf and on emerging pharmacological treatments exploiting combined effects of Lf and classical antifungal drugs. We also reported recent studies on the use of Lf antifungal activity for food and beverage preservation. These new properties have found applications both “in vitro” and “in vivo”, opening new scenarios about the use of this protein as an antinfective agent both in translational medicine and biotechnology.
Keywords: natural immunity